2001
DOI: 10.2307/1423609
|View full text |Cite
|
Sign up to set email alerts
|

A Disruptive Effect of Bizarreness on Memory for Relational and Contextual Details of Self-Performed and Other-Performed Acts

Abstract: We examined recognition memory for relational and contextual details of bizarre and common acts that were either self-performed or performed by another. The results support previous findings that bizarreness disrupts memory for relational details and provide evidence that bizarreness also disrupts memory of the general context in which objects of actions occurred. The disruptive effects of bizarreness were found in memory for both self-performed and other-performed acts. Although parts of bizarre events are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
15
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
4
15
0
3
Order By: Relevance
“…Cuando se ha estudiado el efecto de lo raro en el reconocimiento, en general no se ha encontrado una superioridad de las imágenes raras sobre las normales (Emmerich & Ackerman, 1979;McDaniel & Einstein, 1986;Worthen & Wood, 2001). Sin embargo, nosotros hemos encontrado, al cabo de un día, que las imágenes raras y mixtas eran superiores a las imágenes normales.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Cuando se ha estudiado el efecto de lo raro en el reconocimiento, en general no se ha encontrado una superioridad de las imágenes raras sobre las normales (Emmerich & Ackerman, 1979;McDaniel & Einstein, 1986;Worthen & Wood, 2001). Sin embargo, nosotros hemos encontrado, al cabo de un día, que las imágenes raras y mixtas eran superiores a las imágenes normales.…”
Section: Discussionunclassified
“…Otros autores McDaniel & Einstein, 1986; no encontraron diferencias en recuerdo entre las imágenes normales puras y las imágenes raras puras. Sin embargo, con listas mixtas, las imágenes raras son más efectivas, a corto plazo, que las imágenes normales, sobre todo si la tarea consiste en un recuerdo libre (Imai & Richman, 1991;Marchal & Nicolas, 2000;McDaniel et al, 2000;Tess, Hutchinson, Treloar & Jenkins, 1999;Worthen & Loveland, 2000-2001. Estos autores, cuando utilizaron las listas mixtas, compararon las imágenes normales con las raras de la misma lista.…”
unclassified
See 1 more Smart Citation
“…To the extent that ongoing experience happens to activate relevant portions of prior history, buffered information comes within reach of contextual assimilation through countercurrent interaction in a manner similar to that already described for experience in the "continuity condition." No strategy, of course, can provide contextual matches where none exist, as indicated by poor memory performance for truly bizarre information (Worthen and Wood, 2001). The same interaction with the variance supplied by ongoing experience will prevent the integration/ storage process from "getting stuck" in local minima.…”
Section: E Time and Epistemic Changementioning
confidence: 99%
“…Although many studies (Einstein & McDaniel, 1987;Kroll & Tu, 1988;McDaniel, Einstein, DeLosh, May, & Brady, 1995;Richman, 1994) have shown that components of bizarre events may be remembered better than components of common events, recent studies indicate that bizarre memory fragments are more likely to be falsely recalled (Worthen & Loveland, 2001;Worthen & Roark, in press) and falsely recognized (Worthen & Wood, 2001a, 2001b in an incorrect semantic context than are common memory fragments. Furthermore, research on recognition memory (e.g., Mohr, Engelkamp, & Zimmer, 1989;Worthen & Wood, 2001a, 2001b has demonstrated that a more liberal response criterion is used when people make judgments about bizarre than about common memories.…”
mentioning
confidence: 99%